Woven coronary artery with acquired etiology: the natural history documented by serial angiography and optical coherence tomography - Jiannan Li; Xiaoli Wang; Chen Liu; Peng Zhou; Hanjun Zhao (BMC Cardiovascular Disorders, 2024)
Abstract Woven coronary artery (WCA) is a rare anomaly and its etiology remains speculative. Both congenital and acquired factors are considered to be concerned with the pathogenesis. In a 35-year-old man, the tissue characteristics of WCA were evaluated by optical coherence tomography. Serial coronary angiography indicated that acquired factor is the cause, and thrombus recanalization is the most likely pathological mechanism.